2019
DOI: 10.5195/dpj.2019.256
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Development of a Dialogic Whole-class Discussion Genre

Abstract: Prior research across disciplines has established the value of dialogic, whole-class discussions. Previous studies have often defined discussions in opposition to the notorious triadic pattern called recitation, or IRE/F, focusing on variations to the teacher’s initiating question or evaluative follow-up on students’ responses. Recent scholarship has also identified variations on recitations and dialogic discussions that suggest these categories might be flexible, containing types of interaction associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…When teachers have sought to move past monologic structures, changes are evident. In a U.S. classroom, Sherry (2019) found that Mr. Weber -the PST featured in the study -would include IRE/non-dialogic practices at times, yet managed to break through the pattern, enabling increased high student engagement and successful classroom talk. Similarly, a study in the eastern US reported how a third-grade teacher used forms associated with recitation but still found ways to promote a dialogic stance that functioned to support learning (Boyd & Markarian, 2015).…”
Section: From Recitation To Dialogic Instructionmentioning
confidence: 99%
“…When teachers have sought to move past monologic structures, changes are evident. In a U.S. classroom, Sherry (2019) found that Mr. Weber -the PST featured in the study -would include IRE/non-dialogic practices at times, yet managed to break through the pattern, enabling increased high student engagement and successful classroom talk. Similarly, a study in the eastern US reported how a third-grade teacher used forms associated with recitation but still found ways to promote a dialogic stance that functioned to support learning (Boyd & Markarian, 2015).…”
Section: From Recitation To Dialogic Instructionmentioning
confidence: 99%